Implementasi SPMI di SDN Wonotingal dapat Menumbuhkan Penguatan Karakter Pendidik dan Peserta Didik - Darsimah Darsimah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
Implementation of an internal quality assurance system, schools are encouraged to make improvements internally by involving various related parties so that there are participation and responsibility of each party. Improving the quality of schools is carried out systemically, planned, measured, and sustainable. Quality is everyone's business, not only the responsibility of the principal or a certain group. All parties work together to realize the vision and mission of the school through their respective roles. In addition, school activities to strengthen character education through heart training (ethics), fitness (aesthetics), mind thinking (literacy), and sports (kinesthetic) with public support and collaboration between schools, families, communities that become government programs of the National Movement Mental Revolution.